Penatalaksanaan IMD pada Ibu Postpartum Sectio Caesarea Mempengaruhi Status Gizi dan Kecepatan Produksi ASI : Management of Early Breastfeeding Initiation (IMD) in Post Sectio Caesarea Mother Affecting Nutritional Status and Speed Production of Breast Milk - Syukur, Nursari Abdul; Purwanti, Susi (Poltekkes Kemenkes Palu, 2020)
Many mothers who give birth to Sectio Caesarea (SC) do not Initiate Early Breastfeeding (IMD), which fails exclusive breastfeeding. This study aimed to determine the effect of IMD management in postpartum SC mothers on nutritional status, speed of milk production, and quality of breast milk protein. Method: quantitative research with quasi approach experiment. The research design used was a pre-post-test control non-equivalent control group. A sampling of this study used the Consecutive method sampling with a sample of 20 mothers who gave birth by cesarean section (SC). Hypothesis testing uses the independent t-test and the Mann-Whitney test. The study results showed an influence on the management of IMD in postpartum SC mothers on the speed of ASI production (p-value=0.004) and nutritional status (p-value=0.028). There was no effect of IMD management on postpartum SC mothers on the quality of breast milk protein (p-value = 0.543). This study recommends that the hospital implement an IMD promotion program before the abdominal wall is closed as a form of intervention to increase milk production and maternal nutritional status